(untitled) (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of meningitis cases in Piauí, between the years 2014 to 2021. Methods: Data were collected through the Information System of Notifiable Diseases (Sinan) of the Ministry of Health on reported cases of meningitis in the state from Piauí between the years 2014 to 2021. Data were stratified according to year, gender, age group, etiology and evolution. Results: During the study period, 1,160 cases of meningitis were reported, 62% were male. 51% ran in the 20 – 59 age group; Viral meningitis was the most prevalent (39.5%) and, of the total number of reported cases, 76.9% progressed to medical discharge. Conclusion: There was a decrease in reported cases of meningitis within the period surveyed, this decrease may be directly associated with the pneumococcal vaccine and also with the impact of the Covid-19 pandemic on the regularity of notifications of other diseases of compulsory notification in the years from 2020 and 2021.